Effect of a price discount and consumer education strategy on food and beverage purchases in remote Indigenous Australia: a stepped-wedge randomised controlled trial - Dr Julie Brimblecombe, PhD; Megan Ferguson, MPH; Mark D Chatfield, MSc; Selma C Liberato, PhD; Anthony Gunther; Prof Kylie Ball, PhD; Prof Marj Moodie, DrPH; Edward Miles; Anne Magnus, PGDip; Prof Cliona Ni Mhurchu, PhD; Prof Amanda Jane Leach, PhD; Prof Ross Bailie, MD (Elsevier, 2017)
Background: Evidence is mounting that price discounts can be effective in improving diet. This study examined the effectiveness of a 20% price discount on food and drink purchases with and without consumer education in remote Indigenous Australia. Methods: A 20% discount on fruit, vegetables, water, and artificially sweetened soft drinks was applied for 24 weeks in 20 communities in remote Indigenous Australia where the community store was managed by the Arnhem Land Progress Aboriginal Corporation (ALPA) or Outback Stores (OBS) in a stepped-wedge randomised trial. Communities were randomly allocated to a fixed framework of five sets of four stratified by store association; ten stores (two in each set) were randomly assigned to receive consumer education. A store from each of the ALPA and OBS store groups (contained in separate opaque envelopes) was selected, and stores in turn continued to be consecutively allocated to the fixed store set framework, starting with the first store slot in the first store set, until all stores had been allocated. The effect of the discount on the weight of fruit and vegetables purchased (the primary endpoint) was assessed using weekly store sales data and mixed models per protocol. We did sensitivity analyses by repeating the analyses with the outliers included and repeating the analyses for the primary outcome measure removing each store one at a time. This trial was registered with Australian New Zealand Clinical Trials Registry, number ACTRN12613000694718. Findings: Weekly store sales data on all food and drink products sold in 20 stores were collected from July 1, 2012, to Dec 28, 2014. Price discount alone was associated with a 12·7% (95% CI 4·1-22·1) increase in purchases in grams of fruit and vegetables combined (primary outcome), and a 19·8% (6·2-35·1) increase post discount (after vs before); an effect of 12 g and 18 g per capita per day. Sensitivity analyses did not modify the results for the primary outcome measure. Interpretation: A 20% discount can only increase fruit and vegetable purchases to help protect against obesity and diet related disease to a certain extent. Large discounts might have a greater impact than small discounts. Creative merchandising approaches to consumer education could also be considered alongside fiscal interventions to achieve marked improvements in diet. Funding: Australian National Health and Medical Research Council.